2007
DOI: 10.1242/jeb.011114
|View full text |Cite
|
Sign up to set email alerts
|

Parasites, proteomics and performance: effects of gregarine gut parasites on dragonfly flight muscle composition and function

Abstract: SUMMARY In previous work, we found that dragonflies infected with gregarine gut parasites have reduced muscle power output, loss of lipid oxidation in their flight muscles, and a suite of symptoms similar to mammalian metabolic syndrome. Here, we test the hypothesis that changes in muscle protein composition underlie the observed changes in contractile performance. We found that gregarine infection was associated with a 10-fold average reduction in abundance of a ∼155 kDa fragment of muscle myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…For instance, in D. melanogaster , Lactobacillus plantarum is responsible for mating preference and the composition of the gut microbiota determines mating attractiveness: flies mated preferentially with individuals harbouring similar microbiota, and this preference was probably linked to microbiota‐dependent variation in the cuticle hydrocarbon profile (Sharon et al., ). Similarly, in Libellula pulchella , protozoan parasite infections that affect gut function can alter flight muscle development and decrease flight performance (Schilder & Marden, ). A study of C. capitata showed that feeding gut commensal Enterobacteriaceae bacteria extended host longevity (Behar et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in D. melanogaster , Lactobacillus plantarum is responsible for mating preference and the composition of the gut microbiota determines mating attractiveness: flies mated preferentially with individuals harbouring similar microbiota, and this preference was probably linked to microbiota‐dependent variation in the cuticle hydrocarbon profile (Sharon et al., ). Similarly, in Libellula pulchella , protozoan parasite infections that affect gut function can alter flight muscle development and decrease flight performance (Schilder & Marden, ). A study of C. capitata showed that feeding gut commensal Enterobacteriaceae bacteria extended host longevity (Behar et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle MHC exists as a heterogenous population (12) expressed as two unique isoforms, ␣ and ␤ (26), with post-translational modifications (27)(28)(29)(30)(31). MHC generates 150 tryptic peptides when unmodified and fully cleaved; therefore the endogenous number of MHC charge variants induced by isoforms and PTMs may be greater than 10 4 .…”
Section: Advantages Of Oge As Preparatory Purificationmentioning
confidence: 99%
“…The pre-mRNAs for all three genes are alternatively spliced, leading to the production of mRNAs encoding multiple protein variants that exhibit differential functional characteristics. Consequently, changes in the pattern of troponin T pre-mRNA alternative splicing results in variations in muscle force, power output, and calcium sensitivity in both insects (Fitzhugh et al 1997; Marden et al 2001; Schilder et al 2007) and mammals (Pan et al 1992; Briggs et al 1996; Chaudhuri et al 2005; Sancisi et al 2014). Although little is known about mechanisms involved in regulating alternative splicing of the troponin T pre-mRNA in general, the pattern of rodent Tnnt3 splice variant expression is rapidly altered in young rats in response to changes in effective body mass, e.g.…”
Section: Introductionmentioning
confidence: 99%